2021
DOI: 10.1002/ajcp.12534
|View full text |Cite
|
Sign up to set email alerts
|

Fixes that Fail: A system archetype for examining racialized structures within the food system

Abstract: Access to fresh and healthy food within a neighborhood has been identified as a social mechanism contributing to community health. Grounded in the understanding that challenges related to equity within a food system are both structural and systemic, our research demonstrates how systems thinking can further understandings of food system complexity. Within systems thinking, we provide an illustration of how system archetypes offer an analytic tool for examining complex community issues. We map semi‐structured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…The youth reported their health to largely center around racial disparities in poverty, community infrastructure, crime, and incarceration. This aligned with an additional qualitative study conducted by Benninger, Donley et al (2021) and Benninger, Schmidt‐Sane et al (2021), where community members reported the prevalence of incarceration amongst African Americans in the City of Cleveland to have a detrimental impact not only on the life of the incarcerated individual but on the wellbeing of extended family members.…”
Section: Methodssupporting
confidence: 77%
See 3 more Smart Citations
“…The youth reported their health to largely center around racial disparities in poverty, community infrastructure, crime, and incarceration. This aligned with an additional qualitative study conducted by Benninger, Donley et al (2021) and Benninger, Schmidt‐Sane et al (2021), where community members reported the prevalence of incarceration amongst African Americans in the City of Cleveland to have a detrimental impact not only on the life of the incarcerated individual but on the wellbeing of extended family members.…”
Section: Methodssupporting
confidence: 77%
“…The need for investing in wellpaying jobs, and making them accessible to felons was also identified by the youth as a solution. Both of these findings align with the findings of a system dynamics study within Cleveland, Ohio, which identified a focus on interventions aimed at building wealth and well-paying jobs among marginalized populations as a solution to help alleviate poverty while addressing structural inequities related to high incarceration rates (Benninger, Donley, et al, 2021;.…”
Section: Root Causes Of Incarcerationsupporting
confidence: 76%
See 2 more Smart Citations
“…Although underutilized, it is believed that engaging in collaborative development of SD models by drawing on diverse perspectives of stakeholders can generate collective understanding of health problems that can lead to preventive solutions (Cilenti et al, 2019). For example, SD GMB approaches have been employed in diverse health domains such as inequities in neighborhood food access (Benninger et al, 2021) and community viral load of HIV (Weeks et al, 2017). In the context of maternal health, the SD GMB process can be especially powerful and has been used to generate SD models that capture key feedback mechanisms that shape maternal health disparities (Hovmand, 2014; Skouteris et al, 2015; Sooka & Rwashana‐Semwanga, 2011).…”
Section: Introductionmentioning
confidence: 99%